Ester-substituted copolymer-based ternary semitransparent polymer solar cells with enhanced FF and PCE. (16th August 2021) - Zhu, Kun; Wang, Xiangkun; He, Yan; Zhai, Xiaohua; Gao, Caiyun; Wang, Quanliang; Jing, Xin; Yu, Liangmin; Sun, Mingliang
Abstract: Ternary polymer solar cells (PSCs) are one of the most promising high-efficiency photovoltaic devices with advantages of simple solution fabrication and single-junction structure. Herein, we fabricated ternary PSCs with PC71 BM as the third component, and ester-polymer PFTzTT-3TC as donor and ITIC as host acceptor. So after treatment-annealing, ternary devices based on PFTzTT-3TC: ITIC: PC71 BM (1:1:0.05) exhibited a prominently increased V OC of 0.93 V and PCE of 8.87%. The optimal devices (1:1:0.30) delivers a state of art FF of 71.76%, which is over 22% higher than the value of 58.40% in binary devices. Ternary semitransparent solar cells (1:1:0.25, 15 and 20 nm Ag as cathode) produced a PCE of 6.49% and 7.18% and an AVT of 11.91% and 9.29%, respectively. Our work demonstrated that ternary strategy is a promising solution to improve photovoltaic parameters simultaneously though rational selection of matched fullerene and non-fullerene acceptors. Graphical abstract: Image 1 Highlights: The FF of ternary OSC was obviously improved by the additional PC71 BM from 58.40% to 71.76%. An enhanced PCE of 8.95% was achieved in the 30 wt% PC71 BM incorporated ternary OSC. Applying ester-polymer into ternary semitransparent PSCs was reported firstly.